The Impact of Feminist Approaches on Women's Career Work Performance - Pini Pitria; Netrawati; Zadrian Ardi (Journal Of Psychology, Counseling And Education, 2025)
This journal aims to describe the impact of the feminist approach on the work performance of career women. The feminist approach has had a significant impact on career women's work performance, by helping to overcome barriers such as discrimination and gender inequality. By highlighting the importance of gender equality and challenging social norms that limit women's progress, feminism has promoted a more inclusive and respectful work culture. However, different approaches to feminism have different approaches to how to address these issues, and some approaches have generated controversy and criticism. Overall, the feminist approach has played an important role in improving the work performance of career women, but there is still a path to go to achieve full equality. Data collection is carried out by documenting all articles that have research. The artifacts used in this study were 10 national journal articles obtained from the google scholar database using the Harzing's Publish or Perish application. This SLR analysis allows for a deep understanding of the feminist approach, the work performance of career women. The findings of this literature review provide valuable insights for women, especially career women.